Prevalence of the use of artificial nipples in children under one year old - Nunes, Andréa Cristina Lins (2012)
An exploratory descriptive cross-sectional study with quantitative approach, carried out from the secondary database of the Second Research of Breastfeeding Prevalence in Brazilian capitals and the Federal District in 2009. We aimed to evaluate the prevalence of the use of artificial nipples in children under one year old in six sanitary districts (SD) of Recife-PE, Brazil. The study included 3,120 children, of whom 1,894 (60.7%) used bottle-feeding and 1,310 (41.9%) used a pacifier. The use of bottle-feeding in each SD ranged from 56% in the SD I and II, and 63.2% in the SD IV. The use of pacifier had a reduced number compared to bottle-feeding, SD III presented 44.7% and the districts I and II had 40.6%. We observed that it is necessary to provide further clarification to the mothers about the harmful effects of these habits on breastfeeding, child health and on the breastfeeding process.